Composite indices of human well-being: Past, present, and future - Mark McGillivray; Farhad Noorbakhsh (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2004)
This paper surveys the various composite well-being indices that have been inter-country assessments over the last 40 or so years, including the well known Human Development Index (HDI). A number of issues are considered, including the choice of components, component weights, scale equivalence, non-linearity, correlations among components and the policy relevance of such measures. A number of these issues are examined in the context of a critical review of the many criticisms of the HDI and the United Nations Development Programme's responses to these criticisms (some involving changes to the design of the index). A basic premise of the paper is that indices used for international well-being comparisons should be relevant to the policies and individual priorities of countries. Possible directions for the future design and application of composite well being indicators are identified, including adoption of country-specific variables, participatory, country and time variant component weighting schemes and the inclusion of human security measures.
Keywords: I31; D63; C43; C21; 330; human well-being; composite well-being indices; income per capita; Human Development Index; Physical Quality of Life Index; Entwicklungsindikator; Theorie